Minimally invasive techniques for surgical treatment of sacrococcygeal pilonidal disease - Dubenko, D. Y.; Honza, R. V. (General Surgery, 2024)
Sacrococcygeal pilonidal disease (SPD) is a common disease that affects mainly young men and leads to a decrease in their quality of life and a long‑term loss of working capacity. According to the available statistical data, the disease prevalence in Europe and North America ranges from 26 to 40 cases per 100,000 people. Objective — to determine the effectiveness of minimally invasive techniques for surgical treatment of chronic and recurrent forms of SPD. Materials and methods. The study included 23 patients with SPD. It was clinical prospective, with a follow‑up period of 18 months. The evaluation criteria were defined as recurrences, the frequency of postoperative complications, the severity of the pain syndrome, the patient’s self‑assessment of the cosmetic effect, the duration of hospitalisation, and the duration of surgery. The results. The recurrence rate during the 18 months of observation was 39.1%. The overall frequency of postoperative complications was 21.7%. The median duration of surgery was 20 (CI 95% 15—25) minutes, and the median duration of hospitalisation was 2 (CI 95% 1—3) days. The median score of the pain syndrome according to the modified visual analogue scale was 5 (CI 95% 4—5) points on the 0th postoperative day, 3 (CI 95% 3—4) points on the third postoperative day, and 2 (CI 95% 2—2) points on the fifth postoperative day. The cosmetic effect of surgical intervention was rated as rather dissatisfied (17.4%), rather satisfied (52.2%), and completely satisfied (30.4%). Conclusions. Minimally invasive techniques are effective for the surgical treatment of chronic and recurrent forms of sacrococcygeal pilonidal disease, reducing both the inpatient period and the surgery duration. Minimally invasive surgical treatment for chronic and recurrent forms of sacrococcygeal pilonidal disease has been observed to cause a moderate pain syndrome in the early postoperative period while contributing to satisfactory cosmetic results in the remote period. The surgical treatment of chronic and recurrent forms of sacrococcygeal pilonidal disease with minimally invasive techniques has been found to result in a relatively high recurrence rate (39.1% over 18 months of follow‑up).